2003
DOI: 10.1046/j.1528-1157.2003.33502.x
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Thalamic Mediation of Experimental Seizures: Selective EEG Spectral Coherence

Abstract: Summary:Purpose: Physiological evidence has shown that the anterior thalamus (AN) and its associated efferents/ afferents constitute an important propagation pathway for pentylenetetrazol (PTZ)-mediated generalized seizures in rodents. Previous work demonstrated metabolic, physical, chemical, and electrical stimulation data supporting a role for AN in the expression of PTZ seizures. We now extend these observations through examination of neuroelectric signal indicators during seizure epochs. We show that the E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 49 publications
3
31
0
Order By: Relevance
“…It is conceivable that stimulation site at the anterior part of ANT complex modulates the critical nodes in the seizure propagation pathways. In fact, experimental evidence suggests that ANT plays a major role in seizure spread and generalization in pentylenetetrazole (PTZ) model in rats [16,23]. Stimulation at anterior aspect of ANT using currently available DBS devices reaches most likely the anteriomedial (AM) and the anterior principal (Apr) subnuclei ( Figure 2B).…”
Section: Discussionmentioning
confidence: 99%
“…It is conceivable that stimulation site at the anterior part of ANT complex modulates the critical nodes in the seizure propagation pathways. In fact, experimental evidence suggests that ANT plays a major role in seizure spread and generalization in pentylenetetrazole (PTZ) model in rats [16,23]. Stimulation at anterior aspect of ANT using currently available DBS devices reaches most likely the anteriomedial (AM) and the anterior principal (Apr) subnuclei ( Figure 2B).…”
Section: Discussionmentioning
confidence: 99%
“…Electroencephalographic data and fMRI results have shown that the anterior nuclei of thalamus and their interaction with the cortex play an important role in the genesis of convulsions to pentylenetetrazol [10,27]. In addition, realization of myoclonic convulsions involves most limbic structures, including the hippocampus, which have tight connections with the anterior nuclei of the thalamus.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently the treated rats showed significant behavioral ameliorations with reduced abnormal neurogenesis in the hippocampus. Anterior thalamus may be a good target of electrical stimulation for epilepsy, in that the suppression of anterior thalamic activity seems to limit the propagation pathways for generalized seizures [59]. Alternatively, the substantia nigra pars reticulata, subthalamic nucleus, cerebellum and cerebral cortex may be other targets for electrical stimulation when contemplating with arresting seizure propagation against epilepsy [60–62].…”
Section: Basic Research and Clinical Application For Epilepsymentioning
confidence: 99%